Daring to dream: Targeting lipoprotein(a) as a causal and risk-enhancing factor - Marlys L. Koschinsky; Erik S.G. Stroes; Florian Kronenberg (Elsevier, 2023)
Lipoprotein(a) [Lp(a)], a distinct lipoprotein class, has become a major focus for cardiovascular research. This review is written in light of the recent guideline and consensus statements on Lp(a) and focuses on 1) the causal association between Lp(a) and cardiovascular outcomes, 2) the potential mechanisms by which elevated Lp(a) contributes to cardiovascular diseases, 3) the metabolic insights on the production and clearance of Lp(a) and 4) the current and future therapeutic approaches to lower Lp(a) concentrations. The concentrations of Lp(a) are under strict genetic control. There exists a continuous relationship between the Lp(a) concentrations and risk for various endpoints of atherosclerotic cardiovascular disease (ASCVD). One in five people in the Caucasian population is considered to have increased Lp(a) concentrations; the prevalence of elevated Lp(a) is even higher in black populations. This makes Lp(a) a cardiovascular risk factor of major public health relevance. Besides the association between Lp(a) and myocardial infarction, the relationship with aortic valve stenosis has become a major focus of research during the last decade. Genetic studies provided strong support for a causal association between Lp(a) and cardiovascular outcomes: carriers of genetic variants associated with lifelong increased Lp(a) concentration are significantly more frequent in patients with ASCVD. This has triggered the development of drugs that can specifically lower Lp(a) concentrations: mRNA-targeting therapies such as anti-sense oligonucleotide (ASO) therapies and short interfering RNA (siRNA) therapies have opened new avenues to lower Lp(a) concentrations more than 95%. Ongoing Phase II and III clinical trials of these compounds are discussed in this review.